Climatic constraints for the maize-soybean system in the humid subtropical region of Argentina - Giménez, Víctor David (2017)
The implementation of two summer crops in the same growing season is a possible alternative for land intensification in areas with a long frost-free period. The aim of this study was to analyse the strategy of land intensification through the implementation of the maize-soybean succession at two locations (Reconquista, 29°09′S 59°40′W and Las Breñas, 27°05′S 61°5′W) of the humid subtropical region of Argentina. CERES-Maize and CROPGRO-Soybean models were used to evaluate the impact of inter-annual variability of climate (36 years) of both locations on rain-fed grain yields of the following productive alternatives: (i) monoculture of maize, (ii) monoculture of soybean and (iii) the succession of a short-cycle maize followed by soybean as the second summer crop (maize-soybean system). The maize-soybean system was evaluated by the method of land equivalent ratio (LER), based on the sum of the relative grain yields of its components. The impact of the inter-annual variability of climate and of “El Niño” or “La Niña” episodes (El Niño Southern Oscillation phenomenon (ENSO)) on LER values was analysed. Simulated yields of maize monoculture (5687 kg ha−1; CV = 49.7% and 5637 kg ha−1; CV = 57.6% at Reconquista and Las Breñas, respectively) were higher than those of the short-cycle maize, especially at Las Breñas (5448 kg ha−1; CV = 49.3% and 2322 kg ha−1; CV = 33.9% at Reconquista and Las Breñas, respectively). Simulated yields of the soybean monoculture were higher (3588 kg ha−1; CV = 26.1% and 2883 kg ha−1; CV = 20.7% at Reconquista and Las Breñas, respectively) that those of the soybean as the second crop (2634 kg ha−1; CV = 38.1% and 2456 kg ha−1; CV = 32.9% at Reconquista and Las Breñas, respectively) at both locations. Average LERs were 1.69 (CV = 11.4%) at Reconquista and 1.41 (CV = 26.1%) at Las Breñas, and the inter-annual variability of LER was mainly determined by grain yields of (i) soybean as the second crop at Reconquista and (ii) maize monoculture at Las Breñas. Soil water content after maize harvest and rainfalls during reproductive period of soybean as the second crop conditioned LER values, but they were generally greater than 1. At Reconquista, LER values were not affected by the different episodes of ENSO phenomenon. By contrast, at Las Breñas, LER values were higher during La Niña episodes (1.48; CV = 26.6%) than during El Niño episodes (1.32; CV = 23.7%) mainly by their effects on grain yields of maize monoculture. Therefore, crop simulation models demonstrate the possibility to intensify land use (40–70%) at two locations of the humid subtropical region of Argentina, by the implementation of the maize-soybean system.